Preservation, Standardization and Information Technology 4.0 of Traditional Gedog Tuban Batik to be Competitive in Marketing During COVID - 19 - KARSAM, Karsam; WIDIANA, Muslichah Erma; WIDYASTUTY, Anak Agung Sagung Alit; HIDAYATI, Kusni (Theoretical and Practical Research in Economic Fields; Vol 13 No 1 (2022): TPREF, Volume XIII, Issue 1(25), Summer 2022, 2022)
One of traditional batiks of Indonesia is Gedog Batik in Kerek District, Tuban. Gedog batik is made from handmade cloths. It makes the surface of the cloth is rough. The lines of the fabric are coarse clearly visible. Thus, the batik motifs tend to be geometrically patterned following the flow of the fabric. With these conditions, the researchers are worried that Gedog Tuban batik will not be able to compete in market. On this basis, this research was conducted to examine efforts to preserve, standardize, and IT 4.0 traditional batik/Gedog batik Tuban in order to be able to compete in today's marketing (COVID -19 pandemic era). The objective was to find ways to preserve, standardize and TI 4.0 traditional batik/Gedog Tuban batik to be able to compete in current marketing (during the COVID-19 pandemic). To answer problems above, the method used was descriptive qualitative. The results of the research showed that, first, several attempts to preserve Gedog Tuban batik in was loving gedog batik, improving the quality of the fabric, developing other functions by combining the batik with other materials, using technology for melting and drying colors to speed up production. Second, in order to be able to compete, it needed to be standardized. Batik standardization includes 7 aspects. Third, it needed to conduct online promotion and marketing with the right segmentation. This research is expected to be able be useful for readers, researchers, and Gedog batik craftsman.